PERAN GURU PAI MENJADIKAN MASJID SEBAGAI PUSAT DAKWAH DAN EDUKASI ISLAM DI ERA KOTEMPORER (STUDI KASUS DI PONDOK PESANTREN AR-ROSYID TULUNGAGUNG) - Hulwana Rosyidah; Zainuddin, Mohammad Riza (LPPM STAI Muhammadiyah Probolinggo, 2024)
The research is motivated by the lack of Islamic preaching in the contemporary era, both in non-Islamic environments and in Islamic boarding school (pesantren) and other dormitory-based Islamic schools, especially within the structures of mosque in these Islamic institutions. From this issue, educators, particularly Islamic Studies teachers (PAI), pla a crucial role in making the mosque a center for Islamic preaching and education in the contemporary era. The research problem formulation is as follows: (1) What is the role of PAI teachers in making mosque a center for Islamic preaching and education in the contemporary era (2) What challenges must a PAI teacher face in fullfilling the role of making the mosque a center for Islamic preaching and education in the contemporary era? (3) What are the factors hindering the success of PAI teachers in making mosque a center for Islamic preaching and education in the contemporary era? (4) What are the solutions to overcome the obstacles to the success of PAI teachers in making mosque a center for Islamic preaching and education in the contemporary era?